RANCANG BANGUN SISTEM KONTROL LEMARI PENGERING PAKAIAN BERBASIS MIKROKONTROLER ATMEGA8535 - Rahmat Fauren; Putra Jaya; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
Design and manufacture of this thesis aims to apply microcontroller-based technology for drying clothes automatically without relying on erratic weather conditions. The closet dryer uses a drying method forced convection, by utilizing the flow of hot fluid to reduce moisture in damp clothing. The closet dryer uses a microcontroller ATMEGA8535 as a controller of heater, fan, and UV lamps based temperature and humidity readings by sensors SHT11. The closet clothes dryer is working until the end of the moisture conditions were legible on the sensor SHT11 is <19% RH. The results of sensor readings and status of clothing  displayed on the LCD 16x2. After the clothes was dried  then  closet dryer will informing status of clothes through a voice module ISD1820. From the results of tests and experiments, closet dryer can dry clothes with a maximum capacity of 3 kg within a period of 1 hour to 3 hours, with the value of the first moisture drying  legible and on the sensor SHT11 is  70-80% RH and 17-19% RH in the end. Keywords: Type of clothing,Microcontroller ATMEGA8535,heater, fan, UV lamp, sensor SHT11, LCD16x2, ISD1820.